Strategic plan formation of a construction organization for sustainable project management - P. V. Zozulya; A. V. Zozulya; T. V. Mezina (Вестник университета, 2023)
Today it is important to develop strategic management in project-oriented companies, which include construction organizations, where it is necessary to combine project management with strategic management mechanisms. To manage the projects of a construction company and in order to ensure its sustainable development, it is necessary to use models, methods and project management tools that need to be integrated into the overall strategic management system of the company. The article presents the strategic planning system of a commercial company in the field of construction and describes its subsystems. The interrelation of strategic management of the organization and project management in a construction organization is studied. In order to ensure sustainable project management, the authors have formed a strategic plan for a construction organization, which includes certain considered in detail stages. The final part of the article contains brief conclusions.